(untitled) (Swiss Medical Weekly, 2017)
AIM OF THE STUDY Preeclampsia (PE) is associated with severe maternal and fetal morbidity in the acute presentation and there is increasing evidence that it is also an important risk factor for cardiovascular disease later in life. Therefore, preventive strategies are of utmost importance. The Fetal Medicine Foundation (FMF) London recently developed a first trimester screening algorithm for placenta-related pregnancy complications, in particular early onset preeclampsia (eoPE) requiring delivery before 34 weeks, and preterm small for gestational age (pSGA), with a birth weight <5th percentile and delivery before 37 weeks of gestation, based on maternal history and characteristics, and biochemical and biophysical parameters. The aim of this study was to test the performance of this algorithm in our setting and to perform an external validation of the screening algorithm. MATERIAL AND METHODS Between September 2013 and April 2016, all consecutive women with singleton pregnancies who agreed to this screening were included in the study. The proposed cut-offs of ≥1:200 for eoPE, and ≥1:150 for pSGA were applied. Risk calculations were performed with Viewpoint® program (GE, Mountainview, CA, USA) and statistical analysis with GraphPad version 5.0 for Windows. RESULTS 1372 women agreed to PE screening; the 1129 with complete data and a live birth were included in this study. Nineteen (1.68%) developed PE: 14 (1.24%) at term (tPE) and 5 (0.44%) preterm (pPE, <37 weeks), including 2 (0.18%) with eoPE. Overall, 97/1129 (8.6%) screened positive for eoPE, including both pregnancies that resulted in eoPE and 4/5 (80%) that resulted in pPE. Forty-nine of 1110 (4.41%) pregnancies without PE resulted in SGA, 3 (0.27%) of them in pSGA. A total of 210/1110 (18.9%) non-PE pregnancies screened positive for pSGA, including 2/3 (66.7%) of the pSGA deliveries and 18/46 (39.1%) of term SGA infants. CONCLUSION Our results show that first trimester PE screening in our population performs well and according to expectations, whereas screening for SGA is associated with a high false positive rate.